Immunological Responses to Envenomation - Ryan, Rachael Y. M.; Seymour, Jamie; Loukas, Alex; Lopez, J. Alejandro; Ikonomopoulou, Maria P.; Miles, John J. (Frontiers in Immunology, 2021)
Venoms are complex mixtures of toxic compounds delivered by bite or sting. In humans, the consequences of envenomation range from innocuous to rapidly lethal. Critical host defence comprises innate and adaptive immune strategies, targeted towards venom detection, neutralisation, detoxification, and symptom resolution. In some instances, venoms mediate immune dysregulation that contributes to the severity of symptoms. This review examines the involvement of immune cell subtypes and mediators, particularly of the dermis, regarding host resistance and venom-induced immunopathology. We further discuss established venom-associated immunopathologies, including allergy and systemic inflammation, and investigate Irukandji syndrome as a potential systemic inflammatory response. Finally, this review summarises existing research presenting venom as a source of immune cell modulators for possible drug development.